STUDI KASUS ASUHAN KEPERAWATAN PADA TN‘Y’DENGAN DIABETES MELITUS TIPE II DI RUANGAN RPD III RSUD ENDE - Anabanu, Yudi Meliaki; Artama, Syaputra (Kelimutu Nursing Journal, 2023)
Diabetes Mellitus (DM) is a disease that occurs due to high blood glucose levels commonly called hyperglycemia. Purpose of case study: To know and carry out the nursing care process at Mr. 'Y' by conducting studies, establishing diagnoses, providing interventions, implementation and evaluation. The results of Mr.'Y' case study found dizzy data clients said dizziness, fatigue and lethargy, shortness of breath, coughing up phlegm, weakness, fatigue, nausea, vomiting, reduced appetite, high blood glucose levels, GDS: 315 mg / dL, received novorapid therapy 4 units / sl, attached O2 nasal cannula 5 lpm, ronkhi breathing, difficult activities, all activities assisted, vomiting approximately 3-4x a day, eat a little, approximately 10 spoons, drink limited water, attached infusion NaCl 0.9% 20 tpm. With health problems instability of blood glucose levels, ineffective airway clearance, ineffective breathing patterns, activity intolerance and risk of nutritional deficits. Interventions are structured based on the nursing problems found. The implementation monitors blood glucose levels, teaches patients effective deep breathing and coughing techniques, monitors sputum, provides warm water, provides oxygen, helps perform simple movements, facilitates simple movements, recommends gradual activity, recommends bed rest, identifies nutritional status, monitors weight, provides foods high in protein and calories, and collaborates with nutritionists. The results of the evaluation were carried out for 3 days to five nursing problems were partially resolved. The conclusion obtained is the importance of the participation of all parties in prevention and care as well as the importance of continuity of care and implementation to improve patient health.